Decreased expression of Glucagon-like peptide-1 receptor and Sodium-glucose co-transporter 2 in patients with proliferative diabetic retinopathy - Chen, Hui; Zhang, Xiongze; Liao, Nanying; Ji, Yuying; Mi, Lan; Gan, Yuhong; Su, Yongyue; Wen, Feng (Frontiers in Endocrinology, 2022)
Purpose: To investigate the expression of Glucagon-like peptide-1 receptor (GLP-1R), sodium-glucose co-transporter (SGLT) 1, SGLT2, Glucose transporter type 1 (GLUT1) and GLUT2 in patients with diabetic retinopathy (DR). Methods: We obtained peripheral blood mononuclear cells (PBMCs) and vitreous samples from 26 proliferative DR (PDR) patients, 25 non-proliferative DR (NPDR) patients, 25 non-DR (NDR) patients, and 26 nondiabetic patients with idiopathic epiretinal membranes (ERMs, control). The protein level and mRNA expression level of GLP-1R were quantified by immunoblot and qRT-PCR and the levels of SGLT1, SGLT2, GLUT1, and GLUT2 expression were determined by PCR. Their association with clinical parameters and PBMCs/vitreous cytokine was analyzed. Furthermore, immunofluorescence staining of GLP-1R and SGLT2 was carried out on samples of fibrovascular membranes (FVMs) retrieved from 26 patients with PDR and 26 patients with ERMs. Results: The transcriptional levels of GLP-1R and SGLT2 in PBMCs were significantly more decreased in PDR patients than in patients without DR and controls, which was simultaneously associated with an increased level of expression of tumor necrosis factor (TNF)-α and interferon (IFN)-γ . The expression levels of GLUT1 and GLUT2 were tightly correlated with their SGLT partners, respectively. Further, Immunofluorescence staining showed no positive staining of GLP-1R and SGLT2 was detected in the FVMs from PDR. Conclusions: GLP-1R and SGLT2 were significantly decreased in PDR patients which was associated with an increased level of expression of TNF-α and IFN-γ. These findings implicate that defective GLP-1R and SGLT2 signaling may potentially correlate with immune response cytokines in patients with PDR.